Evaluation of fixation devices for resistance of bending and rotations in supracondylar femoral fracture fixation in dogs - Aithal, H P; Singh, G R (The Indian Journal of Animal Sciences, 2012)
Transverse supracondylar femoral fracture was done in 20 dogs, divided equally in groups, A, B, C and D. Fixation was done using cross intramedullary pins (group A), single pin passed through the intercondyloid fossa (group B), standard stainless steel plate (group C) and properly contoured horn plate (group D). Intramedullary pins (groups A and B) could resist bending forces more effectively compared to plates (groups C and D) and maximum bending was recorded in stainless steel plated animals. Rotation of the distal fragment was more with single pin fixation (group B) than any other group. Horn plating effectively counteracted both rotational and bending forces and thus provided rigid fracture fixation.